Interaction between the μ-opioid receptor gene and the number of heavy drinking peers on alcohol use - Zaso, Michelle J. (Alcohol Clin Exp Res, 2017)
BACKGROUND: The presence of heavy drinking peers may trigger genetic vulnerabilities to alcohol use. Limited correlational findings, albeit mixed as a function of age, suggest that carriers of a μ-opioid receptor (OPRM1) G allele may be more vulnerable than noncarriers to alcohol-promoting perceived peer environments. However, research has not yet examined such genetic susceptibility to actual (rather than perceived) peer environments through an experimental, ad libitum alcohol administration design. The current study examined whether OPRM1 modulates the effects of heavy drinking group size on alcohol consumption and explored potential mediators of such OPRM1-based differences. METHODS: Caucasian young adult moderate to heavy drinkers (N = 116; mean age = 22 years [SD = 2.21], 49% female) were randomly assigned to consume alcohol in the presence of none, one, or three heavy drinking peer confederates. RESULTS: Results showed no significant moderating effects of OPRM1 in the relationship between the number (or presence) of heavy drinking peers and voluntary alcohol consumption (partial η(2) = .01). This result remained the same after controlling for sex, age, and typical drinking quantity as well as their two-way interactions with OPRM1 and social drinking condition. In addition, OPRM1 did not moderate the peer influence on any proposed mediating variables, including craving for alcohol and subjective responses to alcohol. CONCLUSIONS: Findings suggest no OPRM1-based susceptibility to the number of heavy drinking peers, adding to the existing mixed findings from correlational studies. Future research on OPRM1-related susceptibility to alcohol-promoting peer environments through meta-analytic synthesis and both experimental and prospective, multi-wave designs is needed to resolve these mixed findings.